INFLUENCE ANALYSIS OF ORGANIZATIONAL FACTORS ON WORKPLACE BEHAVIOR IN THE IMPLEMENTATION OF RECORDING AND REPORTING PATIENT SAFETY INCIDENTS AT X HOSPITAL IN SURABAYA - Permatasari, Eska Distia; Devi, Yuli Puspita; Handriyanto, Candra Ferdian; Prameswari, Riski Dwi (Lux Mensana: Journal of Scientific Health, 2023)
Introductions. Work behavior is characterized by the implementation of recording and reporting patient safety incidents in accordance with applicable procedures. The problem in this research is the delay in recording and reporting patient safety incidents at Hospital This research aims to analyze the influence of organizational factors (perceived organizational support, organizational culture, ethical work climate, and trust in management) on workplace behavior in the implementation of IKP recording and reporting at Hospital X Surabaya. Method. This study used a cross-sectional design. The research was conducted in 35 work units at Hospital X Surabaya involving 77 work unit members as informants. Primary data collection using a questionnaire was carried out to measure all variables. Meanwhile, workplace behavior is measured using primary data using a questionnaire supported by using secondary data in the form of IKP reports. Meanwhile, workplace behavior is measured using primary data using a questionnaire supported by using secondary data in the form of Patient Safety Incident reports. Results & Analysis. The research results show that there are variables that have a p-value smaller than 0.05. Caring (dummy variable) from the ethical work climate variable (p-value=0.002). Conclusion. There are several recommendations given based on the results of this research. First, increasing cooperation between work unit members who support patient safety behavior related to recording and reporting patient safety incidents. Second, develop programs and policies related to the implementation of recording and reporting patient safety incidents.